2D hydraulic modelling of diversion headworks under extreme flood conditions: A case study of Sunkoshi hydropower project - Bhandari, Anup; Aryal, Aaditya; Joshi, Gaurav; Bimali, Bidhan; Baniya, Binisha; Aryal, Anuj; Chhetri, Rajendra Bahadur; Devkota, Nirajan (Journal of Innovations in Engineering Education, 2026)
This study examines the hydraulic performance and operational vulnerabilities of the Sunkoshi Hydropower Plant in Nepal through two-dimensional (2D) hydraulic modeling. The objectives include analyzing flow dynamics under various operational conditions, optimizing gate management for flood resilience, and maintaining the minimum ecological flow required to ensure environmental needs. Employing historical hydrological data (1965-2012) from the Department of Hydrology and Meteorology, Nepal, and a high-resolution Digital Elevation Model (DEM), the study simulates flood scenarios (10 to 100–year return periods) and operational configuration of the barrage and intake gate with 2D HEC-RAS Modeling. The findings show that during extreme floods, water depths and velocities significantly surpass the design limits, increasing the risks of structural damage and environmental disruption. The findings highlight the necessity of adaptive gate operations, structural reinforcements, and ecological flow considerations to enhance resilience and sustainability. The methodology provides a replicable framework for such hydropower projects in mountainous regions, contributing to sustainable hydropower development.